Examining the Impact of Energy Use, Economic Growth, and Forest Area on CO2 Emissions: Consequences for Achieving the SDGs - Amalia, Mutiara Friska; Junianto, Raihan Rahmanda; Kartiasih, Fitri; Rahmadani, Rizky (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2024)
Climate change can be caused by both natural and human activities. Human activities are the main factor causing climate change that is getting worse such as deforestation, industrialization, transportation, and so on. Climate change that occurs continuously can cause various health risks, global food security, decreased biodiversity, and environmental damage to economic development. Climate change also needs to be studied in the application of SDGs to realize sustainable development targets. The purpose of this study is to examine the relationship between economic growth, energy consumption, and forest area to CO2 emissions in Indonesia from 1990-2022 and find out what the implications are with the achievement of SDGs on climate change. This study applies the VECM analysis method to get an overview of the long-term balance and short-term relationship of the four variables. The results obtained are that forest area only affects CO2 emissions in the long term, while economic growth only affects CO2 emissions in the short term. Meanwhile, the energy consumption variable affects CO2 emissions in both the short and long term. Therefore, handling from various parties and policies from the government are needed to realize environmentally friendly development to achieve sustainable development goals in the future.